2017
DOI: 10.1364/oe.25.015028
|View full text |Cite
|
Sign up to set email alerts
|

ASK-based spatial multiplexing RGB scheme using symbol-dependent self-interference for detection

Abstract: We propose a vsible light communication scheme utilizing red, green and blue light-emitting diodes (LEDs) and three color-tuned photodiodes. Amplitude shift keying modulation is considered, and its effect on light emission in terms of flickering, dimming, and color rendering is discussed. The presence of interference at each photodiode generated by the other two colors is used to improve detection since interference is symbol-dependent. Moreover, the capability of the photodiodes to follow the LEDs speed is co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Besides the intensity of light, the wavelength of emitted light can also be used as an additional dimension to convey information leading to several new modulation techniques such as color shift keying (CSK) [4] and color intensity modulation (CIM) [5]. However, wavelength modulation leads to increase the complexity of the transmission and detection hardware as color light sources and multiple color lenses/filters need to be employed [6].…”
Section: Introductionmentioning
confidence: 99%
“…Besides the intensity of light, the wavelength of emitted light can also be used as an additional dimension to convey information leading to several new modulation techniques such as color shift keying (CSK) [4] and color intensity modulation (CIM) [5]. However, wavelength modulation leads to increase the complexity of the transmission and detection hardware as color light sources and multiple color lenses/filters need to be employed [6].…”
Section: Introductionmentioning
confidence: 99%
“…If not different specified, the SNR in the simulations is equal to 23 dB corresponding to an emitting power of 1 W and distance between transmitter and receiver of 2.9 m. To explain better, the distance we reported is that from green LED, in the middle between red and blue, and the central PD having a green filter in front of it. We refer for modeling moth LEDs and PDS to the ones used in [8], Luxeon Star Rebel for LEDs and Vishay BPW34. Moreover, 5 synchronization symbols are used for training the semiblind equalizer and the µ lp learning factor is set to 10 −3 .…”
Section: Numerical Resultsmentioning
confidence: 99%
“…Thus it is possible to infer that the RS-STE has a more robust behavior over FS-STE when few reference symbols are available and the interference is high, along with the benefit of being less computational complex. Last, both TE and STE are compared with the zero-forcing (ZF) equalizer developed for ASK modulation in RGB transmission in [8]. In order to provide an unfair comparison for our technique, only for ZF, we assume to be in the case of perfect channel knowledge at the receiver.…”
Section: Numerical Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Wu et al reported an eye-safe red/green/blue (RGB) LD based VLC system for white-light communication, achieving a data rate of 8 Gbit/s [6]. Multicolor VLC systems using spatial multiplexing and color shift keying have been reported [13,14].…”
Section: Introductionmentioning
confidence: 99%